Implementation of Sak Etap in Tangkit Baru Jambi Agrotourism Msmes - Khoirany; Wiwik Tiswiyanti; Reni Yustien (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the application of accounting based on SAK ETAP to UMKM Agrotourism in Tangkit Baru Village. This qualitative descriptive study analyzed the results of the interview process and the research instruments that were distributed. The results of this study found that the UKM Agrotourism in Tangkit Baru Village had not fully implemented financial accounting based on SAK ETAP. There are internal factors and external factors that underlie this. The internal factor is due to their lack of understanding regarding accounting records based on SAK ETAP. While the external factor is the lack of supervision from related institutions